2020
DOI: 10.2147/dddt.s245267
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Expression and Therapeutic Potential of Checkpoint Kinase 2 in Laryngeal Squamous Cell Carcinoma</p>

Abstract: Introduction: Laryngeal squamous cell carcinoma (LSCC) is the most common histological subtype of laryngeal cancer. The involved molecular mechanisms and suitable therapeutic targets for LSCC still need to be further investigated. Checkpoint kinase 2 (CHK2) participates in several cellular physiology pathways and plays a role in tumor progression. However, the roles of CHK2 in LSCC remain unclear. Methods: mRNA expression data were obtained from The Cancer Genome Atlas (TCGA) database, and bioinformatic analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…However, a phase I dose-escalation study reported that AZD7762 + gemcitabine yielded limited efficacy in patients with metastatic or unresectable advanced solid tumors, and the risk of adverse cardiotoxicity outweighed the treatment benefit, resulting in research discontinuation [64], which suggests that more clinical trials are needed to determine whether AZD7762 can be applied for the treatment of human tumors. BML-277 (a CHK2 inhibitor) was reported to inhibit the growth of laryngeal squamous cell cancer cells [65]. Likewise, Hseih et al [66] found that BML-277 successfully inhibited the growth of oxaliplatin-resistant CRC cells in vitro and in vivo tumor models.…”
Section: Atm/chk2/p53 Pathway Inhibitorsmentioning
confidence: 99%
“…However, a phase I dose-escalation study reported that AZD7762 + gemcitabine yielded limited efficacy in patients with metastatic or unresectable advanced solid tumors, and the risk of adverse cardiotoxicity outweighed the treatment benefit, resulting in research discontinuation [64], which suggests that more clinical trials are needed to determine whether AZD7762 can be applied for the treatment of human tumors. BML-277 (a CHK2 inhibitor) was reported to inhibit the growth of laryngeal squamous cell cancer cells [65]. Likewise, Hseih et al [66] found that BML-277 successfully inhibited the growth of oxaliplatin-resistant CRC cells in vitro and in vivo tumor models.…”
Section: Atm/chk2/p53 Pathway Inhibitorsmentioning
confidence: 99%